Barriers and facilitators to exchanging health information: a systematic review. (April 2016) - Eden, Karen B.; Totten, Annette M.; Kassakian, Steven Z.; Gorman, Paul N.; McDonagh, Marian S.; Devine, Beth; Pappas, Miranda; Daeges, Monica; Woods, Susan; Hersh, William R.
Highlights: HIE that did not meet provider needs or had poor workflow hindered use. Incomplete patient data was consistently a barrier in US studies. Highest HIE use was in sites with proxy users supporting clinicians. Thoughtful workflows and inclusion of users early in HIE design facilitated use. Abstract: Objectives: We conducted a systematic review of studies assessing facilitators and barriers to use of health information exchange (HIE). Methods: We searched MEDLINE, PsycINFO, CINAHL, and the Cochrane Library databases between January 1990 and February 2015 using terms related to HIE. English-language studies that identified barriers and facilitators of actual HIE were included. Data on study design, risk of bias, setting, geographic location, characteristics of the HIE, perceived barriers and facilitators to use were extracted and confirmed. Results: Ten cross-sectional, seven multiple-site case studies, and two before-after studies that included data from several sources (surveys, interviews, focus groups, and observations of users) evaluated perceived barriers and facilitators to HIE use. The most commonly cited barriers to HIE use were incomplete information, inefficient workflow, and reports that the exchanged information that did not meet the needs of users. The review identified several facilitators to use. Discussion: Incomplete patient information was consistently mentioned in the studies conducted in the US but not mentioned in the few studies conducted outside of the US that take a collective approach toward healthcare. Individual patients and practices in the US may exercise the right to participate (or not) in HIE which effects the completeness of patient information available to be exchanged. Workflow structure and user roles are key but understudied. Conclusions: We identified several facilitators in the studies that showed promise in promoting electronic health data exchange: obtaining more complete patient information; thoughtful workflow that folds in HIE; and inclusion of users early in implementation.